Field‐aligned current response to solar indices. Issue 5 (31st May 2017) - Edwards, Thom R.; Weimer, D. R.; Tobiska, W. K.; Olsen, Nils
Abstract: Magnetometer data from three satellite missions have been used to analyze and identify the effects of varying solar radiation on the magnitudes and locations of field‐aligned currents in the Earth's upper atmosphere. Data from the CHAMP, Ørsted, and Swarm satellite missions have been brought together to provide a database spanning a 15 year period. The extensive time frame has been augmented by data from the ACE satellite, as well as a number of indices of solar radiation. This data set has been sorted by a number of solar wind, interplanetary magnetic field, and solar radiation indices to provide measurements for the field‐aligned current structures in both hemispheres for arbitrary seasonal tilts. In addition, routines have been developed to extract the total current for different regions of the current structures, including regions 0, 1, and 2. Results from this study have been used to evaluate the effects of variations in four different solar indices on the total current in different regions of the polar cap. While the solar indices do not have major influence on the total current of the polar cap when compared to solar wind and interplanetary magnetic field parameters, it does appear that there is a nonlinear response to increasing F 10.7, M 10.7, and S 10.7 solar indices. Surprisingly, there appears to be a very linear response as Y 10.7 solar index increases. Key Points: Field‐aligned current does not always have a linear relationship to increasing solar index A new method of field‐aligned current region identification and totaling has been developed The summer hemisphere draws current away from the winter hemisphere